The Role of Perceived Normative Legitimacy on the Growth Orientation of Women Entrepreneurs in Turkey - Boz Semerci, Anil (Senate Hall, 2020)
This study aims to demonstrate the role of entrepreneurs' achievement motivation and the confirmation of women entrepreneurship in society on their growth orientation. The norms related to women entrepreneurship are distinctive from the legitimation of entrepreneurship and are more related to societies' gender-based cultural contexts. Although recent years witnessed some egalitarian changes concerning the stereotypical roles of women and men in Turkey, it is considered a society where traditional gender roles are still dominant. As such, the country represents an appropriate population to research women entrepreneurs. The data were obtained from 224 women entrepreneurs working in various sectors in Turkey. Hierarchical regression analysis was conducted to test the hypotheses. The results indicate a moderating role of perceived normative legitimacy of women entrepreneurship between the achievement motivation and growth-orientation of women-owned small and medium-sized enterprises (SMEs). That is, normative legitimacy yields a stronger positive relationship with the growth orientation of women entrepreneurs who possess a high need for achievement, compared to women entrepreneurs with a low need for achievement. These results are crucial in understanding the achievement motivation of women and the environment's normative structure in one of the emerging economies. It would also help improve the awareness of both the motivational profiles of women entrepreneurs, and the social context found in Turkey that women entrepreneurs work in.
Keywords: achievement motivation|growth|growth-orientation|legitimacy|normative legitimacy